Stream fish ecology from a landscape ecology perspective - Brejão, Gabriel Lourenço [UNESP]; Leal, Cecília Gontijo; Gerhard, Pedro (Oecologia Australis, 2021)
Landscape ecology emphasizes the interaction between spatial patterns and ecological processes, i.e., the consequences of spatial heterogeneity across various scales. It is an interdisciplinary science that seeks to understand the relationships between ecological patterns and processes considering different spatial and temporal scales. This understanding has been supported by the rapid development of a methodological framework, largely based on Geographic Information Systems (GIS). Thus, it has allowed understanding how ecological processes are affected by anthropogenic activities that trigger profound changes in ecosystems, such as habitat loss and fragmentation. Although commonly applied to studies in terrestrial ecosystems, there is a time lag in both theoretical development and methodological adaptation of landscape ecology applied to studies in streams, especially in Brazil. Methodological adaptations are necessary considering the particularities of aquatic environments in relation to terrestrial ones. For example, streams have a hierarchical spatial organization that results in local conditions dependent on the regional context. In fact, streams are connected to the landscape in which they are inserted through multiple spatial and temporal scales. This hydrologic connectivity, and the low ratio/proportion of aquatic/terrestrial areas, in turn results in anthropogenic impacts accumulating along the hydrographic networks. Considering the above, the objectives of this chapter are: (1) Introduce the general concepts of landscape ecology; (2) Present the main methods of spatial data acquisition and management relevant to stream approaches; (3) Describe the spatial and temporal scales relevant to stream ecology and (4) Discuss the potential of landscape ecology to assess human impacts on streams. Landscape ecology has much to offer to the study of stream fish in Brazil and has shown to be a promising approach for advancing this frontier of knowledge.
A ecologia de peixes de riacho sob a perspectiva da ecologia de paisagens
Keywords: Ecotone; GIS; Hierarchical organization; River landscape; Spatial and temporal scales